Ryzyko w ocenie projektów inwestycyjnych - Nieplowicz, Maria (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2007)
Risk is an immanent feature of every economic venture. The paper presents the type of risk connected with investment projects as well as methods used to estimate the risk of investment project. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1178, s. 76-81